Effectiveness of Scientific Approach in Science Learning with PBL Setting to Empower Science Process Skills - PRASASTI, PINKAN AMITA TRI (Bioedukasi: Jurnal Pendidikan Biologi, 2016)
The purpose of this study was to determine the effectiveness of Scientific Approach to learning science by setting Problem Based Learning (PBL) to empower Science Process Skill (SPS). This study is a quasi-experimental research with Posttest Only Control Group Design which divided into two groups: an experimental group using a Scientific Approach to setting PBL and control groups using expository method and experiment. The population are 124 second semester students of the 2015/2016 academic year. Sample was selected randomly from classess, and two classes was selected, i.e II/F class consisted of 38 students was selected as experimental class, and 36 students of the II/D class was determined as control class. Data of Science Process Skills tested by t-test. Results of analysis of test of hypothesis with a significance level of 5%, shows that the result of significance at p = 0.000 with t-test = 0.016. It means the students' SPS in the experimental class was 83.64, or higher than the control class (73.32). It can be concluded that the Scientific Approach on learning science by setting Problem Based Learning as the method had revealed as an approach to improve Science Process Skill of students.